Prevalence of bipolar disorder in multiple sclerosis: a systematic review and meta-analysis. Issue 2 (16th December 2020) - Joseph, Boney; Nandakumar, Aiswarya L; Ahmed, Ahmed T; Gopal, Neethu; Murad, M Hassan; Frye, Mark A; Tobin, W Oliver; Singh, Balwinder
Abstract : Background: Multiple sclerosis (MS) is a chronic disabling, demyelinating disease of the central nervous system and is often associated with psychiatric comorbidities. Some studies suggest increased prevalence of bipolar disorder (BD) in MS. Objective: To conduct a systematic review and meta-analysis assessing the prevalence of BD in adults with MS. Methods: We registered this review with PROSPERO and searched electronic databases (Ovid MEDLINE, Central, Embase, PsycINFO and Scopus) for eligible studies from earliest inception to October 2020. Prevalence data of BD in adult patients with MS were extracted. Meta-analysis was conducted using random-effects model. Findings: Of the 802 articles that were screened, 23 studies enrolling a total of 68 796 patients were included in the systematic review and meta-analysis. The pooled prevalence rate of BD in patients with MS was 2.95% (95% CI 2.12% to 4.09%) with higher prevalence in the Americas versus Europe. The lifetime prevalence of BD was 8.4% in patients with MS. Subgroup analysis showed a higher prevalence of BD in MS in females (7.03%) than in males (5.64%), which did not reach statistical significance (p=0.53). Conclusions: This meta-analysis suggests a high lifetime prevalence of BD in patients with MS. Patients with MS should be routinely screened for BD. Further assessment of bipolar comorbidity in MS through prospective studies may help in developing effective management strategies and may improve treatment outcomes in patients with MS.